2021
DOI: 10.1007/s10518-020-01021-9
|View full text |Cite
|
Sign up to set email alerts
|

A computational platform to assess liquefaction-induced loss at critical infrastructures scale

Abstract: In the framework of the multi-disciplinary LIQUEFACT project, funded under the European Commission's Horizon 2020 program, the LIQUEFACT Reference Guide software has been developed, incorporating both data and methodologies collected and elaborated in the project's various work packages. Specifically, this refers to liquefaction hazard maps, methodologies and results of liquefaction vulnerability analysis for both building typologies and critical infrastructures, liquefaction mitigation measures as well as cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The liquefaction CBA model was developed as part of a wider RAIF that used an action research methodology to develop, test and refine LIQUEFACT project tools within a built asset management model (Jones et al , 2021). The CBA tool was developed and tested during a two-day workshop (16–17 April 2019) during which the impact of earthquake-induced liquefaction on a hypothetical hospital scenario was modelled and the alternative soil mitigation options were evaluated, using the LIQUEFACT-LRG software (Meslem et al , 2021). The workshop was structured around the CBA process model (Figure 1) and involved detailed discussions between researchers to explore the usability of the CBA from an end-user perspective (each researcher took a different end-user perspective depending on their research background).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The liquefaction CBA model was developed as part of a wider RAIF that used an action research methodology to develop, test and refine LIQUEFACT project tools within a built asset management model (Jones et al , 2021). The CBA tool was developed and tested during a two-day workshop (16–17 April 2019) during which the impact of earthquake-induced liquefaction on a hypothetical hospital scenario was modelled and the alternative soil mitigation options were evaluated, using the LIQUEFACT-LRG software (Meslem et al , 2021). The workshop was structured around the CBA process model (Figure 1) and involved detailed discussions between researchers to explore the usability of the CBA from an end-user perspective (each researcher took a different end-user perspective depending on their research background).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the severity of the liquefaction, structures can undergo damage such as stretching, hogging, dishing, racking/twisting, tilting, global and differential settlement (Van Ballegooy et al , 2014). In addition to damage to buildings and consequential business disruption (Meslem et al , 2021), liquefaction can, in very rare cases, result in death or serious injury to citizens (Daniell et al , 2017; Marano et al , 2010). Analysing losses since 1900 onwards, Daniell et al (2017) reported 3 deaths during the 1995 Kobe event; 2 deaths during the 1964 Niigata; and 16 deaths associated with 1935 Taiwan liquefaction event.…”
Section: Introductionmentioning
confidence: 99%
“…It is also interesting to mention the research developed by Johnson et al [14] in which the use of probabilistic risk analysis (PRA) for critical infrastructure is proposed. Technological innovation also makes it possible to process data capable of defining resilient models of critical infrastructure as clarified by Meslem et al [15] who developed a customized framework/software based on the outcome of the risk and cost-benefit analysis relating to the liquefaction risk. Furthermore, Veeraraghavan et al [16] have developed a software to monitor CIs, in this case an open-source software for seismic risk assessment.…”
Section: Cluster#1 "Risk Assessment" (39 Documents)mentioning
confidence: 99%
“…For this reason, it has been termed the macro-mechanism approach. The procedure presented here has been applied in an extensive parametric study described in Viana da Fonseca et al (2018) for the development of the fragility functions for the loss assessment LIQUEFACT software (Meslem et al 2019), and to assess liquefaction-induced loss at critical infrastructure as described by Meslem et al (2021).…”
Section: Introductionmentioning
confidence: 99%